2022
DOI: 10.1002/ajmg.a.62854
|View full text |Cite
|
Sign up to set email alerts
|

Disparities and outcomes of patients living with Down Syndrome undergoing healthcare transitions from pediatric to adult care: A scoping review

Abstract: Down Syndrome (DS) is one of the most common chromosomal disorders worldwide, and people with DS experience more co-morbidities and have poorer health outcomes compared to the general population. An area that is not well understood is how patients with DS transition from pediatric to adult care, as well as the details, barriers, and difficulties of these transitions for patients. Hence, we aimed to provide a scoping review of the literature in PubMed, Scopus, and CINAHL on the topic of healthcare transitions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Several barriers to effective HCT have been identified (Table 3) and include limited or lack of insurance coverage, income/financial concerns, lack of service coordination, lack of support from ancillary staff (eg nursing, social work, and case management), healthcare culture differences, work involved in transferring and accessing medical records, difficulty obtaining reimbursement for extended clinic appointments, lack of provider knowledge and comfort caring for individuals with special healthcare needs, poor communication between the healthcare provider and family, lack of communication and anticipatory guidance about the HCT process, and family stress and comfort with medical complexities. 2,3,26,63,64 Notably, Gray et al 65 found that a prominent barrier to HCT reported by patients and families is relationships. Patients are often reluctant to leave their pediatric care team and have difficulty accessing knowledgeable adult providers whom they trust with their concerns.…”
Section: Components Of a Healthcare Transition Program And Associated...mentioning
confidence: 99%
“…Several barriers to effective HCT have been identified (Table 3) and include limited or lack of insurance coverage, income/financial concerns, lack of service coordination, lack of support from ancillary staff (eg nursing, social work, and case management), healthcare culture differences, work involved in transferring and accessing medical records, difficulty obtaining reimbursement for extended clinic appointments, lack of provider knowledge and comfort caring for individuals with special healthcare needs, poor communication between the healthcare provider and family, lack of communication and anticipatory guidance about the HCT process, and family stress and comfort with medical complexities. 2,3,26,63,64 Notably, Gray et al 65 found that a prominent barrier to HCT reported by patients and families is relationships. Patients are often reluctant to leave their pediatric care team and have difficulty accessing knowledgeable adult providers whom they trust with their concerns.…”
Section: Components Of a Healthcare Transition Program And Associated...mentioning
confidence: 99%
“…The neurodevelopmental and cognitive profiles observed in individuals with Down syndrome are characterized by significant diversity, presenting unique challenges and opportunities for diagnosis, management, and support [22]. Comorbidities associated with Down syndrome further contribute to the complexity of providing comprehensive care to this population [23][24][25]. Cognitive impairment in individuals with Down syndrome can range from mild (with an IQ between 50 and 70) to moderate (with an IQ between 35 and 50), and occasionally, it can be severe (with an IQ between 20 and 35) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The execution of transition is not an overnight event but rather a purposeful and planned process that equips young adults with the tools to navigate adult healthcare with confidence. For youth with Down syndrome, a comprehensive and longitudinal transition into adult oriented healthcare is especially important, as several gaps currently exist that compromise their access to and ease of mobility in adult healthcare contexts (Varshney et al, 2022).…”
Section: Introductionmentioning
confidence: 99%